Comprehending and Countering Hybrid Warfare Strategies by Utilizing the Principles of Sun Tzu. Issue 2 (4th March 2022) - Ploumis, Michail
ABSTRACT: Hybrid and urban warfare are progressively favoured due to mass migration, technological development and the peoples' low standard of living. This article examines asymmetric as well as hybrid and urban warfare, it provides examples of their implementation from the recent past in Crimea (2014) and Greece (March 2020) and proposes strategies for countering them in the future in which such threats are expected to thrive, on the basis of the principles of the strategy of Sun Tzu.